2022
DOI: 10.3389/fneur.2022.926187
|View full text |Cite
|
Sign up to set email alerts
|

A lesion extending three or more slices as a predictor of progressive infarction in anterior circulation small subcortical infarction

Abstract: Progressive infarction (PI) is common in small subcortical infarction and may lead to a poor outcome. The purpose of our study is to identify neuroimaging predictors for PI. From April 2017 to December 2020, we enrolled 86 patients with an anterior circulation subcortical infarction within 48 h after onset. Progressive infarction was defined by an increase of ≥ one point in motor power or ≥ two points in the total National Institute of Health Stroke Scale score within 7 days after admission and further confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The layers of slices were defined as a variable because multiple layers represented the enlargement of the infarct volume, leading to neurological deterioration in patients with SVD [ 34 ]. Previous studies indicated that the number of slices significantly differed between patients with and without END [ 15 , 35 ]. However, in the present study, neither BAD nor the visible layers of axial slices on DWI would be associated with the risk of END.…”
Section: Discussionmentioning
confidence: 99%
“…The layers of slices were defined as a variable because multiple layers represented the enlargement of the infarct volume, leading to neurological deterioration in patients with SVD [ 34 ]. Previous studies indicated that the number of slices significantly differed between patients with and without END [ 15 , 35 ]. However, in the present study, neither BAD nor the visible layers of axial slices on DWI would be associated with the risk of END.…”
Section: Discussionmentioning
confidence: 99%
“…ACSSI was defined as a single subcortical infarct supplied from the lenticulostriate artery, Heubner's artery or AchA 6 . PI was defined as an increase of ≥1 point in motor power or ≥2 points in the total NIHSS score within 7 days after admission, and extension of the original infarction was further confirmed by DWI or CT 8 …”
Section: Methodsmentioning
confidence: 99%
“…ACSSI was defined as a single subcortical infarct supplied from the lenticulostriate artery, Heubner's artery or AchA. 6 PI was defined as an increase of ≥1 point in motor power or ≥2 points in the total NIHSS score within 7 days after admission, and extension of the original infarction was further confirmed by DWI or CT. 8 792 ª 2024 The Authors. Annals of Clinical and Translational Neurology published by Wiley Periodicals LLC on behalf of American Neurological Association.…”
Section: Definitionmentioning
confidence: 99%
See 2 more Smart Citations